Mapping the Intellectual Landscape of Mathematical Literacy in Mathematics Education: Thematic Evolution, Collaboration Networks, and Emerging Research Frontiers - Siti Nurfadillah; Arif Abdul Haqq; Ebenezer Bonyah (Edupedia Publisher, 2026)
Purpose – Mathematical literacy has expanded beyond its traditional association with large-scale assessment toward a broader domain encompassing pedagogical, technological, and contextual dimensions. This study maps the development, collaboration structure, thematic evolution, underexplored areas, and emerging research frontiers of mathematical literacy research in mathematics education. Methodology – A systematic literature review integrated with bibliometric analysis was conducted using 281 English-language journal articles indexed in Scopus and published between 2016 and March 2026. Following systematic screening procedures, publication trends and geographical distribution were examined alongside co-authorship, keyword co-occurrence, Total Link Strength, overlay and density visualization, and bibliographic coupling using VOSviewer. Findings – The field shows accelerated publication growth, with the United States and Indonesia as the leading contributors, although international and author collaboration remains uneven and fragmented. Six thematic clusters reveal diversification from assessment-oriented foundations toward pedagogy, digital technology, teacher education, STEM, numeracy, and broader quantitative literacy contexts. Ethnomathematics, gender, early childhood education, and several digital and contextual intersections remain comparatively underexplored. Novelty – This study integrates collaborative, intellectual, temporal, and bibliographic structures to demonstrate that mathematical literacy research is undergoing simultaneous quantitative expansion and intellectual reorganization, rather than merely increasing in publication volume. Significance – The findings provide researchers, mathematics educators, and policymakers with an evidence-based map for strengthening cross-context collaboration, connecting fragmented research themes, and developing culturally responsive, technology-supported, and context-sensitive mathematical literacy research.